The Dark Side of Entrepreneurs' Creativity: Investigating How and When Entrepreneurs' Creativity Increases the Favorability of Potential Opportunities That Harm Nature. (July 2022) - Qin, Xin; Shepherd, Dean A.; Lin, Daomi; Xie, Sujuan; Liang, Xueji; Lin, Shanshan
Entrepreneurs' creativity is the starting point of opportunity identification, exploitation, and innovation, so it is generally lauded by journalists, citizen observers, practitioners, and scholars. However, they may overstate the benefits of creative entrepreneurs while neglecting their potential costs. Building on moral disengagement theory, we theorize that a creative mindset enables entrepreneurs to generate reasons to justify their potentially environment-destroying behaviors (i.e., nature disengagement), which in turn increases their favorability of potential opportunities that harm nature. We first developed and validated a scale for measuring nature disengagement and then conducted two randomized between-subject experiments with active entrepreneurs. The empirical results largely supported our theoretical model of the dark side of creativity in the entrepreneurship context.